The role of disorders of immune processes in the pathogenesis of the formation of periodontitis on the background of experimental pneumonia and their correction tetrazolium - Regeda, S. M. (Journal of Education, Health and Sport, 2017)
Regeda S. M. The role of disorders of immune processes in the pathogenesis of the formation of periodontitis on the background of experimental pneumonia and their correction tetrazolium. Journal of Education, Health and Sport. 2017;7(1):350-358. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.268001 http://ojs.ukw.edu.pl/index.php/johs/article/view/4225 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2017; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.01.2017. Revised 16.01.2017. Accepted: 24.01.2017. UDC: 616.24-002-092:612.013-676 The role of disorders of immune processes in the pathogenesis of the formation of periodontitis on the background of experimental pneumonia and their correction tetrazolium S. M. Regeda Lviv National Medical University named after Danylo Halytsky, Ukraine Health Ministry of Ukraine, Kiev, Ukraine Abstract In a gradual decrease in the content of T-lymphocytes and increased B-lymphocytes and circulating immune complexes (CIC) in the blood for 4-th, 8-th, 10-th and 18-th in the era of the development of periodontitis on the background of experimental pneumonia compared with control. Use (EP) thiotriazoline led to an increase in the level of T-lymphocytes and a decrease in the content of B -lymphocytes and the CIC with periodontitis and EP. Key words: periodontitis, experimental pneumonia, immune system, thiotriazolin.